2022
DOI: 10.3390/ani12040512
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cow Behavior Is Affected by Period, Time of Day and Housing

Abstract: Dairy cow behavior is affected by external and endogenous factors, including time of year, barn microclimate, time of day and housing. However, little is known about the combined effects of these factors. Data were collected on eight farms in Northern Italy during summer, winter and a temperate season. The temperature-humidity index (THI) was recorded using environmental sensors, whereas cow behavior was monitored using leg accelerometers and cameras. Period, time of day and their interaction all significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Recently, interest of farm owners on animal welfare has increased because of the targets for obtaining organic products and gaining more income. Feeding, region, year, climate, indoor conditions and lactation periods may be emphasized to be major factors on animal production (Tančin et al, 2018;Leliveld et al, 2022). Especially, ensuring comfortable ambient in barns where the animals kept for a long period has a principal importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest of farm owners on animal welfare has increased because of the targets for obtaining organic products and gaining more income. Feeding, region, year, climate, indoor conditions and lactation periods may be emphasized to be major factors on animal production (Tančin et al, 2018;Leliveld et al, 2022). Especially, ensuring comfortable ambient in barns where the animals kept for a long period has a principal importance.…”
Section: Introductionmentioning
confidence: 99%
“…However, there may be more detail to the interpretation of lying time than just the number of hours spent lying down in a 24 h period. This is confirmed by the undertaken research, which includes a comparison of the lying time of cows during the day and at night, additionally in connection with different seasons [ 18 , 19 ] and climatic conditions [ 20 , 21 ], a comparison of the lying time of healthy and sick cows, including those with mastitis [ 22 ] and lameness [ 23 ], or lying time of cows during heat stress [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 81%
“…The IFS index complements the previously developed and used research indices related to the assessment of various activities of cows in the barn. The indices, which include CLI (cow lying index), CSI (cow standing index), and CFI (cow feeding index), are the basis for monitoring [ 45 ] and assessing the behavior and comfort of cows in connection with the season, time of day, and housing system [ 19 ], with particular emphasis on the free-stall housing system [ 46 ]. A key element in determining these and other indicators is the behavior of cows in different areas of the barn, identified in terms of the comfort achieved [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As regards the nighttime, about 90% of the hours in the LM and 77% in the HM were characterized by THI higher than the first risk threshold (THI > 62) with potential widespread conditions of thermal heat stress for animals. Leliveld et al ( 2022 ) had realized a study in cow farms in North Italy during 2018–2019, and they showed how high THI during nighttime had a significant negative effect on the lying duration and cows rest more while standing to improve evaporative cooling. This demonstrates the importance of continuous monitoring of the microclimate inside the sheds during the summer, even during the nighttime.…”
Section: Discussionmentioning
confidence: 99%